2020
DOI: 10.1098/rspa.2019.0870
|View full text |Cite
|
Sign up to set email alerts
|

Mimicking the active cochlea with a fluid-coupled array of subwavelength Hopf resonators

Abstract: We present a design for an acoustic metamaterial that mimics the behaviour of the active cochlea. This material is composed of a size-graded array of cylindrical subwavelength resonators, has similar dimensions to the cochlea and is able to per- form frequency separation of audible frequencies. Nonlinear amplification is introduced to the model in order to replicate the behaviour of the cochlear amplifier. This formulation takes the form of a fluid-coupled array of Hopf resonators. We seek solutions in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 69 publications
0
37
0
Order By: Relevance
“…When introducing Riemann's unfinished ear paper, his publisher and friend Jacob Henle wrote an introductory paragraph in which he concluded, no doubt from personal conversation, that "Riemann thought that the mathematical problem to be solved was in fact a hydraulic one" (Riemann, 1984: p. 31), and in the light of Riemann's work on shock waves and the fact that the inner ear is filled with fluid, we can begin to appreciate possible implications. Recent work by the present authors has conjectured about the existence of compressible elements within the fluid-filled cochlea (Ammari & Davies, 2019, 2020bBell, 2003Bell, , 2005Bell, , 2008, a possibility we continue to pursue.…”
Section: Physical Processes In the Earmentioning
confidence: 83%
See 1 more Smart Citation
“…When introducing Riemann's unfinished ear paper, his publisher and friend Jacob Henle wrote an introductory paragraph in which he concluded, no doubt from personal conversation, that "Riemann thought that the mathematical problem to be solved was in fact a hydraulic one" (Riemann, 1984: p. 31), and in the light of Riemann's work on shock waves and the fact that the inner ear is filled with fluid, we can begin to appreciate possible implications. Recent work by the present authors has conjectured about the existence of compressible elements within the fluid-filled cochlea (Ammari & Davies, 2019, 2020bBell, 2003Bell, , 2005Bell, , 2008, a possibility we continue to pursue.…”
Section: Physical Processes In the Earmentioning
confidence: 83%
“…Recent work has looked at the air bubble question theoretically, and the results show that an array of air bubbles, graded in size and surrounded by incompressible fluid, are able to replicate the same "tonotopic" organisation of the cochlea-meaning that the array possesses the same distinctive tuning gradient that the organ displays (Ammari & Davies, 2019, 2020b. The interaction of an air bubble immersed within incompressible fluid would no doubt have been of keen interest to Riemann.…”
Section: Physical Processes In the Earmentioning
confidence: 99%
“…It has been reported that a biomimetic acoustic sensor can separate frequency bands from acquired sound signals, and several studies have leveraged the principle of frequency separation according to location in structures that resemble basilar membranes [25]- [32]. Other studies have implemented resonator arrays with a variety of frequencies by changing either the cantilever length/thickness or the membrane size [33]- [38]. Moreover, the frequency of an input signal from a microphone has been separated by using an electronic circuit [39].…”
Section: Introductionmentioning
confidence: 99%
“…Across the biological world, including in humans, cochleae have remarkable abilities to filter sounds at a very high resolution, over a wide range of volumes and frequencies. This exceptional performance has given rise to a community of researchers seeking to design artificial structures which mimic the function of the cochlea [1,3,9,24,30,34]. These devices are based on the phenomenon known as rainbow trapping, whereby frequencies are separated in graded resonant media.…”
Section: Introductionmentioning
confidence: 99%